2017
DOI: 10.1007/s40091-017-0166-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental static and dynamic tests on a large-scale free-form Voronoi grid shell mock-up in comparison with finite-element method results

Abstract: Grid shells supporting transparent or opaque panels are largely used to cover long-spanned spaces because of their lightness, the easy setup, and economy. This paper presents the results of experimental static and dynamic investigations carried out on a large-scale freeform grid shell mock-up, whose geometry descended from an innovative Voronoi polygonal pattern. Accompanying finite-element method (FEM) simulations followed. To these purposes, a four-step procedure was adopted: (1) a perfect FEM model was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…(2016) studied the static stability of the Voronoi grid structure and concluded that the Voronoi grid structure is not only aesthetically pleasing but also statically efficient. Froli and Laccone (2017) carried out experimental research on a free‐form Voronoi grid structure and confirmed that the Voronoi diagram is an effective grid for spatial grid structure. The Rokko Mountain Observatory in Japan is also designed according to the Voronoi diagram (Su, Wu, Qiao, & Shen, 2019).…”
Section: Introductionmentioning
confidence: 83%
“…(2016) studied the static stability of the Voronoi grid structure and concluded that the Voronoi grid structure is not only aesthetically pleasing but also statically efficient. Froli and Laccone (2017) carried out experimental research on a free‐form Voronoi grid structure and confirmed that the Voronoi diagram is an effective grid for spatial grid structure. The Rokko Mountain Observatory in Japan is also designed according to the Voronoi diagram (Su, Wu, Qiao, & Shen, 2019).…”
Section: Introductionmentioning
confidence: 83%
“…In Figure 18, many planar coil designs for WPT systems are depicted, including rectangular, circular, and hybrid forms. These are applied to boost output and fix transmitter and receiver misalignment problems similarly to structural issues [314]. Additionally, each model's associated benefits and drawbacks are listed in a similar table [315].…”
Section: Coil Designmentioning
confidence: 99%
“…Inspired by lightweight and robust lattice structures that appear in nature, some works addressed the use of a Voronoi mesh for structural purposes at a larger scale. The works Froli & Laccone, 2017;Pietroni et al, 2015;Tonelli et al, 2016 proposed and validated a method for generating a Voronoi mesh, whose cells conform to the principal stress directions of the underlying surface, and are scaled and stretched accordingly. Su et al (2020) developed a morphogenesis method for Voronoi structures of high architectural and structural performances.…”
Section: Voronoi Mesh As a Design Toolmentioning
confidence: 99%